A Comparative Analysis of the Influence of ESG Performance and Controversy on Firm Value : a Comparison of Companies in Indonesia and Malaysia - Tiara Fauza; Riza Reni Yenti (Badan Penerbit STIEPARI Press, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) performance and controversies on firm value in Indonesia and Malaysia, two significant markets with differing regulatory environments. The research addresses three main questions: (1) Does ESG performance enhance firm value? (2) Does ESG controversy reduce firm value? (3) How do ESG performance and controversies differ between the two countries? Using panel data regression analysis, the study analyzes 41 Indonesian and 52 Malaysian non-financial firms (2020–2024) sourced from Refinitiv Eikon. Firm value is measured by Tobin’s Q, while ESG performance and controversies are assessed through composite scores ranging from 0 to 100. The results indicate that ESG performance significantly enhances firm value in Malaysia (β = 0.0387; p < 0.001), likely due to the standardized reporting requirements under the Malaysian Code on Corporate Governance. In contrast, no significant effect is observed in Indonesia (β = 0.0068; p = 0.358), where the adoption of POJK 51/2017 remains voluntary. Regarding ESG controversies, no significant impact on firm value is found in either market (p > 0.05), suggesting that investors are not significantly concerned with sustainability scandals. However, Malaysian firms have superior ESG performance (mean = 58.62 vs. 52.50; p < 0.001), while Indonesian firms experience fewer controversies (mean = 98.60 vs. 96.59; p = 0.038). The study concludes that regulatory frameworks are crucial in transforming ESG commitments into market value, whereas weak enforcement mechanisms may prevent penalties for controversies. The findings highlight the need for ASEAN policymakers to harmonize ESG reporting standards and enhance investor education on sustainability risks.